2000
DOI: 10.1136/thorax.55.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal risk factors for asthma in Finnish adolescent twins

Abstract: Background-Previous studies have suggested that, in addition to genetic liability and environment in early childhood, intrauterine life also influences the risk for asthma beyond childhood. Low birth weight, prematurity, young maternal age, and maternal smoking have all shown an association with asthma. The eVect of perinatal factors on the risk for asthma in relation to familial and social risk factors was studied in a nationwide population-based sample of adolescent twins. In addition to a distribution of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
4
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 31 publications
(33 reference statements)
7
56
4
2
Order By: Relevance
“…As she has summarized in her dissertation, the genetic contribution to variance in liability to both asthma and hay fever was found to be high Räsänen et al, 1998). In addition to corresponding parental disease, a high ponderal index at birth and maternal smoking also proved to be risk factors for asthma (Räsänen et al, 2000), while male gender, small sibship and gestational maturity proved to be independent risk factors for hay fever (Räsänen et al, 1997). The relative contribution of genes vs. environment in disease liability and the effect of perinatal risk factors for asthma and hay fever varied according to parental disease status.…”
Section: Allergy and Asthmamentioning
confidence: 99%
“…As she has summarized in her dissertation, the genetic contribution to variance in liability to both asthma and hay fever was found to be high Räsänen et al, 1998). In addition to corresponding parental disease, a high ponderal index at birth and maternal smoking also proved to be risk factors for asthma (Räsänen et al, 2000), while male gender, small sibship and gestational maturity proved to be independent risk factors for hay fever (Räsänen et al, 1997). The relative contribution of genes vs. environment in disease liability and the effect of perinatal risk factors for asthma and hay fever varied according to parental disease status.…”
Section: Allergy and Asthmamentioning
confidence: 99%
“…Because the occurrence of hay fever among adolescents with farming fathers was distinct from that of children with fathers in the other occupational groups, the other occupational groups' data were pooled. The variables and methods of the present study have been described in more detail previously (Räsänen et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Räsänen and colleagues studied 3065 Finnish twin pairs and found that the heavier twin at birth (as indicated by ponderal index) had an increased risk of asthma at age 16 compared with his or her twin brother or sister (Räsänen at al., 2000). The relationship was stronger in fraternal than in identical twins consistent with common genetic influences on asthma and birthweight.…”
Section: Prevalence and Admission Rates For Asthmamentioning
confidence: 99%